1982
DOI: 10.1177/070674378202700505
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Possible Inverse Relationships between the Occurrence of Rheumatoid Arthritis, Osteoarthritis and Schizophrenia

Abstract: One hundred and eleven inpatients with schizophrenia and 51 with other psychiatric conditions were compared for the frequency of rheumatoid arthritis, other connective tissue disorders and other physical illness. Evidence both of rheumatoid arthritis and osteoarthritis was significantly less in the schizophrenia group. Latex Agglutination Tests were positive to the same extent in both groups. One possible explanation of the findings is that they are due to the reduced frequency of trauma or stress to the joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…This allows the effect of schizophrenia to be studied in isolation. Five of these studies are based in individual psychiatric hospitals ‐ [Mohamed et al, ] Mohamed et al, ; [Ross et al, ]; [Pilkington, ]; [Oken & Schulzer, 1999] Ross et al, ). Two use record‐linkage methods [Baldwin, ]; [Osterberg, ] on international and Swedish populations respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This allows the effect of schizophrenia to be studied in isolation. Five of these studies are based in individual psychiatric hospitals ‐ [Mohamed et al, ] Mohamed et al, ; [Ross et al, ]; [Pilkington, ]; [Oken & Schulzer, 1999] Ross et al, ). Two use record‐linkage methods [Baldwin, ]; [Osterberg, ] on international and Swedish populations respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The finding was replicated more than a dozen times, and various explanations were offered, such as that neuroleptic medications had a protective effect; or that persons with schizophrenia were less likely to report pain; or that life as an inpatient was less physically active and thereby less prone to raising risk for rheumatoid arthritis. Each of these hypotheses was evaluated in studies with research designs that effectively discounted those explanations (Mellsop et al, 1974; Mohamed et al, 1982; Pilkington, 1955; Trevathan and Tatum, 1953). There have been several studies of genes, immune-related factors, and common infections which might explain the inverse association (de la Fontaine et al, 2006; Genevay et al, 2002; Hopkins et al, 1988; Taylor, 1978; Torrey and Yolken, 2001; Wright et al, 1998), including a compelling meta-analysis showing that the antagonist to the receptor of the inflammatory cytokine IL-1 was more prevalent in individuals with schizophrenia, thus protecting them from rheumatoid arthritis (Potvin et al, 2008).…”
Section: Autoimmunity and Schizophreniamentioning
confidence: 99%
“…Numerous studies including several tens of thousands of patients were identified (7,18,85,(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210)(211), the vast majority of which found a decreased frequency of rheumatoid arthritis among people with schizophrenia. Explanations may be of a genetic, environmental (institutionalization and sedentary lifestyle due to negative symptoms), pharmacological (analgesic and anti-inflammatory effects of antipsychotic drugs) and biochemical (histo-imcompatibility factors) nature [for review see (212,213)].…”
Section: Skin and Connective Tissue Diseases (392 Medline Hits)mentioning
confidence: 99%